Anxa2‐ and Ctsd‐knockout CHO cell lines to diminish the risk of contamination with host cell proteins. (22nd April 2019) - Fukuda, Nobuo; Senga, Yukako; Honda, Shinya
Abstract: Chinese hamster ovary (CHO) cells have been used as host cells in the production of a range of recombinant therapeutic proteins, including monoclonal antibodies and Fc‐fusion proteins. Host cell proteins (HCP) represent impurities that must be removed from therapeutic formulations because of their potential risks for immunogenicity. While the majority of HCP impurities are effectively removed in typical downstream purification processes, clearance of a small population of HCP remains challenging. In this study, we knocked out the Anxa2 and Ctsd genes to assess the feasibility of knockout approaches for diminishing the risk of contamination with HCP. Using the CRISPR/Cas9 system, Anxa2 ‐, and Ctsd ‐knockout CHO cell lines were successfully established, and we confirmed the complete elimination of the corresponding HCP in cell lysates. Importantly, all knockout cell lines showed similar growth and viability to those of the wild‐type control during 8 days of cultivation. Thus, knockout of unrequired genes can reduce contamination with HCP in the production of recombinant therapeutic proteins.